Detection of Shiga toxin-producing Escherichia coli, stx1, stx2 and Salmonella by two high resolution melt curve multiplex real-time PCR. (February 2019) - Singh, Prashant; Liu, Yuejiao; Bosilevac, Joseph M.; Mustapha, Azlin
Abstract: In the United States, Shiga toxin-producing Escherichia coli (STEC) O157 and six non-O157 serogroups O26, O45, O103, O111, O121 and O145 are considered adulterants in non-intact beef. Further, Salmonella is responsible for one of the highest numbers of foodborne infections worldwide. Multiple foods, especially meats, are routinely tested for these pathogens using methods like PCR. However, with such a large group of organisms, multiplexing using probe-based PCR assays is expensive due to the need for differently labeled oligonucleotide probes and sophisticated instrumentation. The aim of this study was to design low-cost multiplex real-time PCR assays for the detection of seven STEC serogroups, stx 1, stx 2 genes and virulent Salmonella . Two multiplex real-time PCR melt curve assays with internal amplification controls (IAC) were standardized. The first assay detected E. coli O121, E. coli O145, E. coli O157, stx 1, and stx 2 . The second assay targeted E. coli O26, E. coli O111, E. coli O103, E. coli O45, and Salmonella . Ground beef and beef trim inoculated with 5–27 CFU/325 g of STEC and 9–36 CFU/325 g of Salmonella could be detected following an 8–10 h enrichment at 40 °C ± 2 °C in buffered peptone water containing 8 mg/L vancomycin. The assays showed reproducible results for beef products with different fat contents. These assays do not rely on fluorescent-labeled probes or immunomagnetic beads, yet accurately detect seven STEC serogroups, seven stx gene subtypes and Salmonella, making them suitable for routine testing of STEC and Salmonella in beef. Highlights: Multiplex melting curve PCR to detect STEC, stx subtypes and Salmonella were developed. The assays targeted E. coli O121, O145, O157, O26, O111, O103, O45, Salmonella, stx 1, stx 2 . Beef samples inoculated with 5–27 CFU/325 g of beef could be detected after 8–12 h enrichment. The assays complied with USDA, FSIS recommendations for these pathogens.